ChemInform Abstract: Deep Eutectic Solvents: Synthesis, Properties and Applications. Issue 4 (31st January 2013) - Zhang, Qinghua; De Oliveira Vigier, Karine; Royer, Sebastien; Jerome, Francois
Abstract Review: ca. 200 refs.